Fasilitas, Aksesibilitas Dan Daya Tarik Wisata Terhadap Kepuasan Wisatawan - Sri Handayani; Nanang Wahyudin; Khairiyansyah Khairiyansyah (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
Bangka Belitung is an archipelago province that has various tourist destinations, one of which is Bangka Botanical Garden (BBG) which is an agro tourism area that not only promotes nursery systems, but also other fields such as education, research, sports and tourism. This study aims to determine the effect of facility, accessibility and tourist attractiveness on tourist satisfaction visiting the Bangka Botanical Garden (BBG) Pangkalpinang. This Study uses a quantitative approach with a total sample of 260 respondents, while sampling techniques is non-probability sampling techniques using accidental sampling method. The independent variable in this study consists of facitily, accessibility, and tourist attractiveness, while the dependent variable is tourist satisfaction. Data processing uses multiple linear regression analysis with T test, F and R2 test. The results showed that testing the hypotheses, both partially and simultaneously on facility variables, accessibilities and tourist attractiveness had a positive and significant effect on tourist satisfaction visiting Bangka Botanical Garden (BBG) Pangkalpinang. This indicated that the better the facilities, accessibilities and tourist attractiveness available in the Bangka Botanical Garden (BBG) tourism area of Pangkalpinang, the more tourist satisfaction increase. The coefficient of determination (R2) was 62.7%, which means that the variables of tourist satisfaction can be explained by variable facilities, accessibility and tourist attractiveness.